Simple and Green Preparation of ZnO Blended with Highly Magnetic Silica Sand from Parangtritis Beach as Catalyst for Oxidative Desulfurization of Dibenzothiophene - Wega Trisunaryanti; Safa Annissa Novianti; Dyah Ayu Fatmawati; Triyono Triyono; Maria Ulfa; Didik Prasetyoko (Universitas Gadjah Mada, 2022)
Simple and green preparation of ZnO blended with Parangtritis beach sand (BS) catalysts for oxidative desulfurization of dibenzothiophene (ODS-DBT) has been conducted. The ZnO-BS catalysts were prepared by blending ZnO with beach sand under a weight ratio of 1:1, 1:2, and 1:4, and then heated by microwave (MW) at 540 watts for 30 min, resulting in BS-MW, ZnO-MW, ZnO-BS-1-MW, ZnO-BS-2-MW, and ZnO-BS-4-MW, respectively. As a comparison, the ZnO-BS-1 was also heated by oven at 100 °C for 30 min produced ZnO-BS-1-OV. Each product was characterized by XRF, XRD, FTIR, acidity test by NH3 vapor adsorption, SAA, SEM-EDX, TEM, and magneticity test by an external magnetic field. Furthermore, each material was applied for ODS-DBT, and its product was analyzed by UV-Vis spectrophotometer and FTIR. The results showed that ZnO-BS-1-OV had the highest acidity of 2.3486 mmol/g and produced the highest DBT removal efficiency through the ODS reaction of 81.59%. The use of catalysts in ODS-DBT does not affect the main structure of the treated fuel. Therefore, the combination of ZnO with BS can provide good performance in ODS activity and facilitate the separation of catalysts after the reaction due to its magnetic iron oxide content.